Pentingnya Penanaman Nilai-Nilai Agama Pada Pendidikan Anak Usia Dini Dalam Perspektif Al-Quran - Atin Risnawati; Dian Eka Priyantoro (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
As an educator, he is obliged to be able to create a righteous and righteous generation in accordance with religious values ​​in accordance with. Early childhood education (ECE) is not only on the formal track, but the family and the surrounding environment also provide education for a child. This development of has the Koran as a source of law and science. Apart from that, the Koran also serves as a guideline for living in child rearing. Therefore, the Al-Quran becomes an important guide in the learning process for early childhood in order to produce a superior Islamic generation in the midst of global competition. In this case the author tries to explain the importance of inculcating religious values ​​from the perspective of the Koran in early childhood education. Because early age is the earliest and easiest age for the formation of children's character compared to when the child has reached adolescence. The method used by the author is library research, which explains the theory of children's education, and how to cultivate the values ​​of the Koran from an early age.